Beyond continuity institutional change in advanced political economies - Streeck, Wolfgang, 1946-; Thelen, Kathleen Ann.; ProQuest (Firm) (Oxford ; New York : Oxford University Press, 2005)
"This book examines current theories of institutional change. The chapters highlight the limitations of these theories. Instead a model emerges of contemporary political economies developing in incremental but cumulatively transformative processes"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Institutional economics -- Case studies; Organizational change -- Europe -- Case studies; Capitalism -- Europe -- Case studies; Organizational change -- United States -- Case studies; Capitalism -- United States -- Case studies; Electronic books